2022
DOI: 10.3389/fsoc.2022.806458
|View full text |Cite
|
Sign up to set email alerts
|

Preferences for Income Redistribution in Unequal Contexts: Changes in Latin America Between 2008 and 2018

Abstract: In a developing and highly unequal region like Latin America, it is crucial to understand the determinants that affect people's support for redistribution of resources from the state. A series of theories focused on self-interest have continuously established a negative link between people's income and their support for the reduction of inequalities through redistribution. Despite this, the evidence is scarce and sometimes contradictory while its study in Latin America is almost non-existent. Using data from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 82 publications
(106 reference statements)
0
0
0
Order By: Relevance
“…However, Latin America has placed itself as a scenario that questions the applicability and universality of the mainstream self-interest approach (Dion & Birchfield, 2010). Indeed, it has been found that unlike in developed countries (Finseraas, 2009;Gijsberts, 2002;Schmidt-Catran, 2016), in Latin America, attitudes toward inequality are not primarily determined by the objective socioeconomic position of individuals (Berens, 2015;Bucca, 2016;Franetovic & Castillo, 2021). Scholars have highlighted the relevance of social affinity and political attitudes in peoples' attitudes toward inequality across the region.…”
Section: Understanding Attitudes Toward Inequality In Latin America A...mentioning
confidence: 99%
See 2 more Smart Citations
“…However, Latin America has placed itself as a scenario that questions the applicability and universality of the mainstream self-interest approach (Dion & Birchfield, 2010). Indeed, it has been found that unlike in developed countries (Finseraas, 2009;Gijsberts, 2002;Schmidt-Catran, 2016), in Latin America, attitudes toward inequality are not primarily determined by the objective socioeconomic position of individuals (Berens, 2015;Bucca, 2016;Franetovic & Castillo, 2021). Scholars have highlighted the relevance of social affinity and political attitudes in peoples' attitudes toward inequality across the region.…”
Section: Understanding Attitudes Toward Inequality In Latin America A...mentioning
confidence: 99%
“…For instance, Borges (2022) showed that the cultural diversity of Latin American countries decreases individuals' agreement with redistribution. In addition, Franetovic and Castillo (2021) evidenced that income-based differences in support for redistribution emerge only in certain scenarios of inequality and economic development, while trust in the political system stands out as a more important determinant of it. This behavior within the region adds to a broad literature that destabilizes the direct link between social positions and attitudes toward inequality, emphasizing the importance of cultural norms and normative values (Etzioni, 1988;Feldman & Zaller, 1992), as well as the availability of distributional information in social environments (Dawtry et al, 2015;Lindh et al, 2021;Mijs, 2018).…”
Section: Understanding Attitudes Toward Inequality In Latin America A...mentioning
confidence: 99%
See 1 more Smart Citation